Environmental attitudes and recycling behaviour in primary school age: The role of school and parents - Šorytė, Dovilė; Pakalniškienė, Vilmantė (Psichologija, 2021)
This study aimed to investigate the relationship between environmental attitudes and recycling behaviour in primary school age, and to evaluate the role that school and parents play in the prediction of children’s attitudes and behaviour. Primary school pupils aged 8–11 years (n = 116), their parents and their class teachers participated in the study. During the structured face-to-face interviews, children answered questions about their recycling behaviour and environmental attitudes (i.e. eco-affinity and eco-awareness). Parents provided answers on their recycling behaviour, verbal modelling of the behaviour, incentives used when a child recycles waste, and environmental attitudes, while class teachers provided information about the recycling in children’s school. Structural equation models were tested with a purpose to evaluate the role of different independent variables, i.e. only school, only parental factors, or both, when predicting child recycling behaviour. Results of the study showed that children’s environmental attitudes had no significant links to their recycling behaviour. The only factor that appeared to be significant in the prediction of child behaviour was parental recycling behaviour. Furthermore, recycling in schools predicted pupils’ eco-awareness. Based on the study findings, it would be worthwhile to promote more practical training of pro-environmental behaviour, and to strengthen children’s eco-affinity.